Comparative Evaluation of Flexural Strength of PMMA Reinforced with Graphene (G-CAM) and Monolithic Zirconia - An In Vitro Study - Harshita Sachdev; Mukesh Soni; Alka Gupta; Harsh Chansoria; Megha Patil; Bhavya Sharma; Kritika Kar; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: Optimal flexural strength is a critical prerequisite for materials used in fabricating prosthetic frameworks. The aim of this study was to evaluate and compare the Flexural strength (FS) of two CAD/CAM materials used in dental prostheses, namely polymethyl methacrylate (PMMA) reinforced with graphene (GCAM) and Monolithic Zirconia. Materials and Methods: In this in-vitro experimental study, 40 bar-shaped samples were manufactured by a milling machine and divided into two groups (n = 20/group): Group 1, GCAM; Group 2, Monolithic Zirconia. The specimens were subjected to a three-point bending test until fracture to evaluate Flexural strength. Data was statistically analyzed using an independent samples t-test to compare the two groups at a 0.05 significance level. Results: Compared to GCAM samples, each Monolithic Zirconia sample showed significantly higher values of flexural strength (P < 0.001). Conclusion: The results show that GCAM is a promising material to be used for prosthetic purposes where less strength and greater resiliency are required.